Chikungunya - C. Roxanne Rutledge-Connelly; Christopher N. Mores; Chelsea T. Smartt; Walter J. Tabachnick (EDIS)
ENY-736, a 3-page illustrated fact sheet by C. Roxanne Connelly, Christopher N. Mores, Chelsea T. Smartt, and Walter J. Tabachnick, describes this mosquito-borne virus, what it is, its symptoms, how its transmitted to humans, where it occurs, risk to Floridians, and how it can be prevented. Includes references. Published by the UF Department of Entomology and Nematology, April 2007.